m-7=-13+m

Simple and best practice solution for m-7=-13+m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for m-7=-13+m equation:


Simplifying
m + -7 = -13 + m

Reorder the terms:
-7 + m = -13 + m

Add '-1m' to each side of the equation.
-7 + m + -1m = -13 + m + -1m

Combine like terms: m + -1m = 0
-7 + 0 = -13 + m + -1m
-7 = -13 + m + -1m

Combine like terms: m + -1m = 0
-7 = -13 + 0
-7 = -13

Solving
-7 = -13

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 9x=8x-31 | | 42j+18-19=-28 | | 5y+8=2y+2 | | 5x=-2 | | 4(x+2)=4x-10 | | 3p-1=3x-9 | | 3x^2+12x= | | -4(1+5X)-7(-5+8X)=31 | | 3(x-5)-14=2(x-7)+2 | | 2(s-3)=15 | | x-3+2=0 | | -5(m+10)=100 | | 4(x+7)=36 | | 30=-2(1+2N)+8(N+8) | | -2x-1=7+2x | | 4(3x+15)=0 | | -3s+(-4)=25 | | -7(-5V+1)+5(8+7V)=33 | | 3s+4=25 | | 2(3x-7)=3x-5 | | X+(-4)=8 | | 2x*x^2-16*4x+3=0 | | 5(6+8B)+8(B-5)=-10 | | m-4m+12=3 | | 5x+10=9x+15 | | [(x-2)-5][(x-2)+3]=0 | | 18+2x=-54 | | 17x+64=13 | | -256=8(7X-6)-4X | | 24x+7*8= | | 5a-2+b-3b+2a= | | 5x-3x+40=50 |

Equations solver categories